Teachers' Efforts to Improve Student Achievement in Islamic Religious Education Subjects - Rohima; Torkis Dalimunthe (Rahis Cendekia Indonesia, 2024)
This inquire about looks at the imperative part of Islamic Devout Instruction (PAI) instructors in progressing understudy scholastic accomplishment. By centering on the academic setting, this inquire about distinguishes the methodologies and hones that PAI instructors utilize to contribute emphatically to understudy accomplishment. The writing audit moreover examines the impact of PAI instructors on learning inspiration, character advancement, and the integration of devout values into the learning prepare. The comes about of this inquire about give profitable knowledge into the advancement of compelling PAI learning and the vital part of PAI instructors in making a learning environment that cultivates understudy accomplishment.